2016
DOI: 10.1093/europace/euw145
|View full text |Cite
|
Sign up to set email alerts
|

Cryoablation of atrioventricular nodal re-entrant tachycardia: 7-year follow-up in 515 patients—confirmed safety but very late recurrences occur

Abstract: Cryoablation in AVNRT is safe with a long-term efficacy of 88%; however, very late recurrences occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…In spite of comparable acute procedural success rates between RF and Cryo, a concern regarding Cryo is the procedure's significantly high recurrence rates during long‐term follow‐up . In these studies, the higher recurrence rate of Cryo can possibly be explained by the smaller‐tip (4‐mm) Cryo catheter.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of comparable acute procedural success rates between RF and Cryo, a concern regarding Cryo is the procedure's significantly high recurrence rates during long‐term follow‐up . In these studies, the higher recurrence rate of Cryo can possibly be explained by the smaller‐tip (4‐mm) Cryo catheter.…”
Section: Introductionmentioning
confidence: 99%
“…Friedman et al reported that acute procedural success was achieved in 83% of patients with supraventricular tachycardia (91% for AVNRT, 69% for AVRT, and 67% for AV junction in patients with atrial fibrillation) and long‐term success after 6 months was 91% overall in patients with acute procedural process. The success rate of cryoablation itself in this study was lower than that in the previous studies . There were several factors that might have influenced the results.…”
Section: Discussionmentioning
confidence: 86%
“…11 Cryoablation, on the other hand, is an effective and safe alternative to RFCA, with no permanent AV block reported in the larger studies, and a comparably excellent acute success rate. 9,10,21 However, the long-term recurrences are consistently higher than for RFCA among the published studies. Currently available data from the larger studies on the acute and long-term outcomes of catheter ablation of AVNRT are summarized in Table 1.…”
Section: Current Perspectives On Catheter Ablation Of Avnrtmentioning
confidence: 94%